Investigation on sacrificial pore former removal and mullite binder phase transformation in powder formulations used for preparation of oxide bonded porous SiC ceramics. Issue 12 (15th August 2017) - Dey, Atanu; Kayal, Nijhuma; Innocentini, Murilo D.M.; Chakrabarti, Omprakash
Abstract: Sacrificial pore former removal and mullite binder phase transformation ~ the two major stages of processing of oxide bonded porous SiC ceramics ~ were studied by conducting thermal analysis of the precursor powders (SiC +20 wt% Al2 O3 +15–41 vol% petroleum coke pore former). Kinetic computation of reactions occurring in these stages was done by fitting the non-isothermal DTA data to empirical models. The ceramics prepared from the precursor powders were characterized by the combined approach of chemical and XRD analyses and electron microscopy and the results in combination with the kinetic data were used to explain the formation of the pore phase and the mullite binder phase of the ceramics.